Pronunciation Intelligibility of Nigerian Speakers of English - Idowu, Fiyinfolu Olubunmi (European Scientific Journal, ESJ, 2019)
The study examines the phonological intelligibility of Nigerian speakers of English. Specifically, it investigates the extent to which vowel quality in the speech of Nigerian Speakers of English affects their intelligibility to speakersfrom different contexts.100 evaluators, (international listeners made up of non-Nigerian speakers) transcribed six speech samples from six audio podcasts in which Nigerian speakers delivered speeches. The transcription of the different speech samples served to assess intelligibility at pronunciation level (specifically segmental features). Results revealed that using vowel realisations distinct from the central vowels [ʌ], [ɜ:], and [ə] caused intelligibility problems for international listeners.